Comorbid infections in spondyloarthritis: a modern view of the problem - N. V. Muravyeva; B. S. Belov; M. M. Baranova; T. V. Korotaeva (Современная ревматология)
The review considers the problem of comorbid infections (CIs) in ankylosing spondylitis and psoriatic arthritis (PsA) as the main nosological entities of spondyloarthritis (SpA). It analyzes the frequency of CIs during therapy with biological agents and targeted synthetic disease-modifying anti-rheumatic drugs. It is concluded that the problem of CI in SpA deserves the closest attention. The review also shows the importance of preventive measures for CI in the treatment of SpA. It is in particular noted that in accordance with the updated guidelines of the European League Against Rheumatism and other rheumatology research associations, all patients with immunemediated inflammatory rheumatic diseases (including SpA) on immunosuppressive therapy are recommended to get influenza and pneumococcal vaccines due to the high risk of death from respiratory tract infections. Moreover, vaccination is indicated even for patients with an expected suboptimal response. The review gives the main points of the recommendations of the Medical Board of the National Psoriasis (Ps) Foundation on the use of recombinant Herpes zoster vaccine in patients with Ps/PsA. There is a need for further investigations of the frequency and pattern of CIs and the impact of new therapy options on the prevalence of CIs in patients with SpA. Determination of the effectiveness and safety of vaccination in this patient population should become an important area for future investigations.